Association between social disadvantage and falls in older adults: a longitudinal study - Salcedo Salgado, Juan David; Cigarroa, Igor; Tuesca, Rafael; Touchie, Salim; Acosta, Tania (Revista Cuidarte, 2026)
Highlights • Older adults with lower levels of education and without their own occupation are at a higher risk of falling, highlighting social inequalities accumulated throughout their lives. • Social disadvantages during youth and adulthood significantly influence the risk of falls, in contrast to household conditions in old age. • The study highlights the importance of considering cumulative socioeconomic factors as a key predictor of adverse health events among older adults. • Improving educational and working conditions from early life stages could mitigate risks in old age, such as frailty and recurrent falls. Introduction: The deterioration of social determinants of health across the life course may act as a relevant factor in increasing the risk of frailty and falls, thereby exacerbating social and health problems. Objective: To analyze whether social disadvantages experienced during different stages of life are associated with the occurrence of falls among older adults. Materials and Methods: A prospective study was conducted based on the Seniors-ENRICA-1 cohort, including 2,501 Spanish participants aged 60 years or older. Falls and falls requiring medical attention were considered the study outcomes. Exposure was defined as the level of lifelong social disadvantage, assessed across childhood, youth, adulthood, and old age. Bivariate analyses and logistic regression models adjusted for sociodemographic, clinical, and lifestyle variables were applied. Results: Individuals with low educational attainment were 1.4 times more likely to experience a fall compared to those with higher education. Additionally, individuals without an occupation in adulthood had an 80% higher probability of falling. No significant associations were found with the father’s occupation or with household conditions in old age. Discussion: There is agreement that falls in older adults are associated with accumulated social inequalities, especially low educational attainment and occupation. Variables such as age, lifestyle, and medication use also have an influence. The socioeconomic situation is analyzed from an alternative perspective. Conclusion: Accumulated disadvantages in education and occupation increase the risk of falls in older adults. How to cite this article: Salcedo Salgado Juan David, Cigarroa Igor, Tuesca Rafael, Touchie Salim, Acosta Tania. Association between social disadvantage and falls in older adults: a longitudinal study. Revista Cuidarte. 2026;17(1):e5220. https://doi.org/10.15649/cuidarte.5220